A call for action: Latinxs in social work education. Issue 3 (27th May 2018) - Calvo, Rocío; Ortiz, Larry; Villa, Patricia; Baek, Kelly
ABSTRACT: This study examines the need for a culturally prepared social workforce to serve the nation's largest minority group and provides recommendations to address this burgeoning issue. Using the same goal of population parity established by the 2007 Task Force on Latinos in Social Work Education, the authors (a) present an update on Latinxs presence in social work programs, (b) propose a theoretical framework and a conceptual paradigm to prepare future social workers to properly serve Latinx communities, and (c) introduce a case study designed to systematically address this issue.